A novel bionic-based substructure division method for topology optimization. (February 2021) - Zhang, Fan; Du, Wenfeng; Zhang, Hao
Abstract: In the cantilever plate structure, traditional topology optimization cannot achieve satisfactory results since topological material always focuses on one part while the other parts occupy no or few materials. To overcome this drawback, a bionic-based substructure division method for topology optimization was proposed in this paper. In this method, The designable region of topology optimization was divided into several substructures. The material layout of each subordinate topology design unit was formed for maximizing the total stiffness under a prescribed material usage constraint. The concept and optimization model of the bionic-based substructure division method was constructed. Then, the effectiveness of the method was verified through the example of a cantilever plate by comparison with the traditional topology optimization. Finally, an application example of a cross joint using the bionic-based substructure division method was provided and made by 3D printing technology. The research results show that the bionic-based substructure division method can enhance the guidance of topology optimization in finding reasonable material layout. By this method, the innovative configuration of a lighter cross joint is obtained. The application of this method improves the efficiency and effect of structural optimization.